1998
DOI: 10.4269/ajtmh.1998.58.589
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characterization of American cutaneous leishmaniasis in an endemic region of eastern Venezuela.

Abstract: Abstract. The status of American cutaneous leishmaniasis was investigated from 1985 to 1991 to provide an epidemiologic characterization of the disease in Bergantin, a rural community in the northeastern part of Anzoátegui State, Venezuela. The study revealed the presence of the infection during the period analyzed, with an average incidence of 50.2 cases per 10,000 inhabitants and this number has increased 1.5 times during the last two years. Three villages where clinical cases had been recorded were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…Additionally, in a hospital-based study performed in Samara [12], the incidence rate was 5.5 cases / 10,000 for the year 1994. However, the incidence rate was similar to that reported for Afghanistan [13] (46 per 10,000) and Eastern Venezuela [14] (50.1 per 10,000) but higher than that reported for Turkey (4.6 per 10,000) [15].…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, in a hospital-based study performed in Samara [12], the incidence rate was 5.5 cases / 10,000 for the year 1994. However, the incidence rate was similar to that reported for Afghanistan [13] (46 per 10,000) and Eastern Venezuela [14] (50.1 per 10,000) but higher than that reported for Turkey (4.6 per 10,000) [15].…”
Section: Discussionsupporting
confidence: 80%
“…18 Higher frequency of ACL cases among males between the ages of 15 and 49 has also been reported in other states. [21][22][23] The current study showed that most patients had the cutaneous form of the disease, lived in urban environments and acquired ACL during work or leisure activities. It has been observed that in Latin America and in Brazil a significant decrease in forest areas has led to an ACL increase in urban regions which, consequently, requires new methods of disease control.…”
Section: Discussionmentioning
confidence: 82%
“…The authors however, attributed the antigen-associated discrepancies observed in the results to possible technical problems arising during antigen injection. Jorquera and collaborators (Jorquera et al, 1998), examining human beings from an endemic area for visceral and tegumentary leishmaniosis, also found individuals that selectively responded to preparations containing L. chagasi (8.7%) or to preparations containing a mixture of L. amazonensis, Leishmania venezuelensis and L. braziliensis (23.9%), or to preparations containing both antigens (67.4%). Such variety of responses found in human beings is similar to that observed in this study with dogs.…”
Section: Discussionmentioning
confidence: 93%